(untitled) (Revista Brasileira de Iniciação Científica, 2022)
Echinodorus grandiflorus (EGF) is a medicinal plant found throughout Brazil and popularly used as diuretic and anti-inflammatory. These effects make it promising for the treatment of rheumatoid arthritis (RA), which is a chronic inflammatory disease of the synovial frequently associated with cardiovascular disease. This narrative review described the evidence from studies that observed anti-inflammatory properties of EGF extracts in experimental models of acute inflammation, as well as its efficacy as diuretic, analgesic, vasodilatator and in reducing cholesterol levels also in experimental models. However, studies in experimental models more suitable for RA and clinical trials are still lacking.